Test case prioritization with Jaro-Winkler-Manhattan textual distance - Tumeng, Rooster (2015)
Abstract—Large test suite experiencing requirement changes needs to be ordered through the means of prioritization of its test cases. Conventional techniques focusing on the code availability of a program neglect requirement changes. Through this paper, we propose textual comparisons for test cases through the combination of classical and non-classical textual comparison metrics and elaborate a prioritization algorithm. This method of test prioritization is independent of the code availability and provides a way to perform testing in its absence. We summarize the initial findings of the experiment carried out and draw conclusion on future works.